2021
DOI: 10.3390/cancers13184702
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Selected Adipokines in Ascites and Blood of Ovarian Cancer Patients

Abstract: Ovarian cancer is one of the most common malignancies among women worldwide. The course of the disease is often latent and asymptomatic in the early stages, but as it develops, metastasis occurs, accompanied by accumulation of ascites in the peritoneal cavity. The ascites fluid constitutes a specific microenvironment influencing the processes of carcinogenesis. In ascites, signaling is mediated by various cytokines that control tumor cell proliferation, progression, metastasis, and chemoresistance. Adipokines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…19 IL-8, otherwise called CXCL8, is a critical cytokine that positively regulates neutrophil chemotaxis and inflammation. 20,21 It is secreted by numerous cells, namely, neutrophils, monocytes, endothelial cells and tumour cells. Emerging evidences suggested that the circulating IL-8 levels in tumour patients is strongly associated with worse patient outcome and chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 IL-8, otherwise called CXCL8, is a critical cytokine that positively regulates neutrophil chemotaxis and inflammation. 20,21 It is secreted by numerous cells, namely, neutrophils, monocytes, endothelial cells and tumour cells. Emerging evidences suggested that the circulating IL-8 levels in tumour patients is strongly associated with worse patient outcome and chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐8, otherwise called CXCL8, is a critical cytokine that positively regulates neutrophil chemotaxis and inflammation 20,21 . It is secreted by numerous cells, namely, neutrophils, monocytes, endothelial cells and tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was found from comparative studies (70 ascites and 20 plasma samples) that its concentration is higher in ascites and correlates with its volume. Serum levels in patients with OC (stage I-IV) are the highest after cytoreductive surgery and the lowest after treatment ( 17 ). Sonego et al ( 18 ) observed that high TIMP-1 levels in patients with OC at stage III and IV were associated with reduced OS especially if patients were treated with platinum or bevacizumab.…”
Section: Timp Metallopeptidase Inhibitor 1 (Timp-1)mentioning
confidence: 99%
“…In addition to adipocytes, there are also stromal vascular fraction, adipose-derived stem cells, preadipocytes, macrophages, lymphocytes, eosinophils, mast cells, fibroblasts, and nerve cells [ 27 , 30 , 31 ]. There are four types of AT differentiated by histological structure and function: white adipose tissue (WAT), brown adipose tissue (BAT), beige adipose tissue, and pink adipose tissue [ 27 , 32 ]. WAT, one of the largest organs, is the main energy store of the organism, which captures and accumulates lipids [ 33 ].…”
Section: Characteristics Of Adipose Tissuementioning
confidence: 99%